Vaganova: A Dance Journey from St Petersburg to Leningrad by Vera Krasovskaya. Book Review - Glasstone, Richard (Dance Books Ltd., Alton,Hampshire (UK), 2005)
PALABRAS CLAVE: Agrippina Vaganova.
Dentro del apartado "Compare & Contrast".
Vaganova: A Dance Journey from St Peterburg to Leningrad, Vera Krasovskaya, University Press of Florida, 2005.